Prevalence of Natural Enemies of Red Mite, Tetranychus bioculatus (Wood-Mason) in Marigold Gardens - Taleb, MA; Sardar, MA (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> An investigation was carried out on the natural enemies of red mite, Tetranychus bioculatus in the marigold gardens. Insects and spiders both were found to occur as the predators of red mite. Two species of lady bird beetle viz. Stethorus punctillum, Micraspis discolor and two species of spiders e.g. lynx spider (Oxyopes sp.), long mouth spider (Tetragatha sp.) were encountered. Micraspis discolor and spiders were more than S. punctillum. The abundance of predator population was positively correlated with the abundance of their mite prey. Key words: Natural enemies, red mite, marigold. DOI = 10.3329/jard.v5i1.1467 J Agric Rural Dev 5(1&2), 110-115, June 2007